EKSPANSI TERITORI PADA HUNIAN DI KAMPUNG MOJO KOTA SURAKARTA PASCA PROGRAM UPGRADING - yenni yosita br barus; Fikrian Rafika Dewi; Findara Illa Nursyifa; Ardhya Nareswari; Ahmad Sarwadi (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract: Kampung Mojo is one of the settlements in Surakarta City where the KOTAKU (City Without Slums) program is implemented. This initiative aims to improve the quality of basic infrastructure in slum areas, thereby reducing slum conditions. The program has redesigned the settlements by clear boundaries within residential areas, including the organization of residential layouts, plot arrangements, street spaces, and open spaces. During observations in September 2023, a notable phenomenon emerged regarding how residents use the outdoor spaces of their houses, such as alleys, streets, and leftover land, to accommodate personal and social activities. This research aims to identify the forms and patterns of territorial expansion within residential areas, providing valuable insights for future space management in Kampung Mojo following infrastructure upgrades. The study employs a qualitative approach, with primary data collected through direct observation and interviews at the research site, followed by descriptive analysis. Findings indicate that territorial expansion is a response to the limited available space, where residents utilize surrounding spaces to meet personal needs and create spaces for social gatherings. Keywords: Expansion, Settlements, Post Upgrading Abstrak: Kampung Mojo adalah salah satu kawasan lokasi penanganan KOTAKU (Kota Tanpa Kumuh) di Kota Surakarta.Tujuan program tersebut adalah meningkatkan kualitas infrastruktur dasar sehingga berkurang tingkat kekumuhannya. Kawasan permukiman didesain dengan batas-batas yang jelas pada ruang pembentuk kawasan seperti bentuk dan kavling hunian, jalan lingkungan, dan ruang terbuka yang dapat dimanfaatkan untuk aktivitas sosial. Berdasarkan observasi yang dilakukan pada bulan september 2023, banyak ditemukan fenomena penggunaan ruang di luar hunian seperti gang dan jalan untuk mengakomodasi aktivitas pribadi dan juga sosial.Penelitian ini bertujuan untuk mengidentifikasi bentuk dan pola ekspansi teritori primer (hunian) dan agar dapat menjadi masukan terhadap pengelolaan ruang di Kampung Mojo pasca upgrading. Teknik pengumpulan data yang digunakan pada penelitian ini adalah melalui observasi wawancara yang diambil dari lapangan dan analisis data menggunakan metode penelitian deskriptif kualitatif. Ekspansi teritori yang terjadi di Kampung Mojo baik penataan Tahap 1 dan Tahap 2 pasca upgrading merupakan respon dari keterbatasan ruang di dalam rumah dan kebutuhan ruang komunal untuk aktivitas sosial. Kata Kunci: Ekspansi, Permukiman, Pasca Upgrading